Implementation of Digital Marketing to Enhance the Promotion of Social Activities and Creative Products at Istana Yatim Al Jufri Orphanage Foundation - Tirta Mulyadi; Hari Sandi Atmaja; Eva Amalia; Wahyudi Ilham (PUSLITABMAS-Politeknik Pariwisata Batamc, 2026)
The rapid development of digital technology has significantly transformed communication and promotional activities across various sectors, including social institutions and community-based foundations. Digital marketing has become an important strategy for increasing public awareness, strengthening institutional branding, and expanding the reach of social programs. This community service activity was conducted at Istana Yatim Al Jufri Orphanage Foundation in Batam with the aim of improving the participants’ understanding and skills in utilizing digital marketing to promote social activities and creative products. The implementation method consisted of preparation, training, practical mentoring, and evaluation stages. The materials delivered included the introduction of digital marketing, social media utilization, content creation techniques, branding strategies, and basic digital promotion practices. The results showed that participants experienced increased knowledge regarding digital marketing concepts and improved skills in managing social media and creating promotional content. Participants also demonstrated enthusiasm in applying digital platforms to support social activities and creative product promotion. Furthermore, this activity has strong sustainability potential through continuous mentoring programs, social media optimization, and the development of digital-based creative entrepreneurship. The program also strengthened collaboration between higher education institutions and social organizations in supporting community empowerment through digital transformation. Keywords: digital marketing, social promotion, social media, creative products, community service